Efficient route to synthesizing a biocompatible delivery system undergoing morphological changes upon solvent variation. (13th March 2023) - Mandal, Piyali; Mukherjee, Madhumita; Shunmugam, Raja
Abstract : Self-assembled thiobarbiturate-functionalized poly(methyl methacrylate) nanoparticles were synthesized, characterized and tested for their encapsulation and release capabilities. Abstract : The self-assembly of a biocompatible amphiphilic homopolymer, thiobarbiturate-functionalized poly(methyl methacrylate) (PMMA-TBA), mediated by water and other cosolvents has been demonstrated here. The synthesis and thorough characterization of the resulting polymeric nanoparticles were documented using conventional spectroscopic techniques, followed by detailed morphological investigations carried out using dynamic light scattering (DLS), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and cryo-transmission electron microscopy (cryo-TEM) analysis. Thorough microscopy studies confirmed fascinating morphologies of nano-aggregates with variable sizes. Super-aggregates were further successfully explored via encapsulation and release studies. The low cytotoxicity of the nano-architectures at high concentrations confirmed their suitability for biomedical applications.